0467 Preference for Digital CBTI: Changes due to the COVID-19 Pandemic in a Randomized Controlled Trial of CBTI for Middle Aged and Older Adults. (25th May 2022) - Gumport, Nicole; Tutek, Joshua; Simpson, Norah; Tully, Isabelle; Dietch, Jessica; Zulman, Donna; Rosas, Lisa; Palaniappan, Latha; Manber, Rachel
Abstract: Introduction: Digital CBTI programs are effective at treating symptoms of insomnia. They also have the potential to increase treatment reach, convenience, and affordability for patients, and to reduce long wait times for behavioral sleep medicine providers. The COVID-19 pandemic has instigated an increased reliance on the use of technology for many. Thus, this study evaluates middle aged and older adults before and during the COVID-19 pandemic to assess: (1) differences in treatment modality preference (digital vs. therapist-led CBTI) and (2) sleep-related predictors of treatment modality preference. Methods: Participants were older adults (N=229, 74% female, mean age=63.14) who were enrolled in the RCT of the Effectiveness of Stepped-Care Sleep Therapy in General Practice (RESTING) study. At baseline, participants rated if they would prefer to access CBTI digitally or with a CBTI therapist, either in person or via telemedicine. After March 2020, in person was no longer listed as an option. Participants completed the Insomnia Severity Index (ISI) and a two-week sleep diary that allowed for an assessment of total sleep time (TST), sleep onset latency (SOL), and wake after sleep onset (WASO). Analyses compared responses to these items from participants completing assessments before March 2020 (Pre-Covid; n=74, 65% female, mean age=62.52) and after March 2020 (During-Covid; n=155, 78% female, mean age=63.44). Results: Pre-Covid, 26% of participants preferred digital treatment, 47% of participants preferred a therapist-led intervention, and 27% did not express a preference. During-Covid, 35% of participants preferred digital treatment, 32% of participants preferred a therapist-led intervention, and 32% did not express a preference. This difference was statistically significant (c2=4.24, p=0.04). Responses were not significantly different between the first six months and the most recent six months of the pandemic (p=0.60). None of the sleep measures (ISI, TST, SOL, WASO) were associated with treatment modality preference in the full sample, Pre-Covid, or During-Covid. Conclusion: The COVID-19 pandemic was associated with increased preference for digital CBTI among patients who are 50 and older, regardless of insomnia severity. Findings suggest that digital CBTI may be an acceptable treatment to many individuals with insomnia, thus increasing its dissemination potential. Support (If Any): R01AG057500 and T32MH019938